Moderacja asymetrii władzy organizacyjnej w przedsiębiorstwie sieciowym - Perechuda, Kazimierz (The moderation instruments in the network, 2006)
In the paper are presented: management dilemmas in the network organizations, identification of the basic issues of the network moderation, the types of the network, the levels of the network, the evolution of the network, the moderation instruments in the network
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 482-486